Phản ứng của tầng điện lý xích đạo quan sát tại Tp. Hồ Chí Minh đối với bão từ 17-19/8/2003 - Lan, Hoàng Thái (Vietnam Journal of Earth Sciences, 2005)
The effects of magnetic storm on the ionosphere are complex and large deviations from apparent average behaviors. These effects are common in any particular storm. The interest in understanding the response of the upper atmosphere to geomagnetic storms has stemmed from the need to predict the ionospheric response. This need arises for practical reasons: communication systems require signals to pass from ground - to - ground using HF radio via the ionosphere, and from ground - to satellite through the ionosphere at higher frequencies. Ionospheric disturbances may cause the influence on everyday human activity. In the low latitude regions, where many people live, the investigations related to these disturbances are of great importance. Ionospheric sounding measurements from Ho Chi Minh City (Long.106.3°E; Lat.105°E, dip lat. 2.9°N), Vietnam, are presented for the period August 17 to 19, 2003. The observatory equipped with a Canadian Advanced Digital lonosonde (CADI) and a Japanese Fluxgate Magnetometer. The period selected for the present study related to storm effects on equatorial F-region parameters and irregularities includes the intense geomagnetic storm on August 18. A comparative study of the Fregion ionospheric data from the Hoc Mon observatory for both the quiet and disturbed conditions are presented and discussed in this communication . It is pointed out that on the magnetic disturbed period the foF2 values are increased mostly during daytime. The h'F variations show a rapid and large uplifting during nighttime. Simultaneous with the maximum depression of magnetic field, the falls in h'F and foF2 were observed. The variations in peak heights hpF2 during magnetic storm period are not as striking as those in h'F, but are often characterized by significant fluctuations.